An Outcomes-Based Framework for Integrating Academics With Student Life to Promote the Development of Undergraduate Students’ Non-cognitive Skills - Ahuja, Abha; Netto, Camila L. M.; Terrana, Alexandra; Stein, Geneva M.; Kern, Suzanne E.; Steiner, Mara; Kim, Rachel; Krupnick Walsh, Kayla (Frontiers in Education, 2022)
Non-cognitive skills are essential for success in a variety of settings but are not commonly taught and assessed in undergraduate curricula. The challenge for curricular integration of non-cognitive skills stems from varying interpretations of what it means to apply a specific skill effectively. In addition, teaching these skills requires going beyond the foregrounded academic content in traditional coursework. Here we present the integrated, outcomes-based approach to teaching non-cognitive skills designed and used at Minerva University. We have articulated a core set of skills and concepts as Foundational Learning Outcomes that all students learn in their first year and continue to apply throughout their four years, receiving feedback and scores across academic, disciplinary, and real-world, experiential learning contexts. We provide examples of the Learning Outcomes, detailing their introduction and application in various contexts across the four-year arc of their college experience. We identify aspects of our approach that can be generalized and implemented in different settings, from individual courses to programs, departments, or entire institutions.